LTE network expansion under unlimited traffic packages in colleges and universities - Shuai WANG; Yi LI; Maolin CHEN; Guifang XU (Dianxin kexue)
After the launch of the unlimited traffic package,the demand for LTE network capacity has increased dra-matically,and the business model of college student users has also changed.Aiming to change the business traffic of college users before and after the launch of the unlimited traffic package,through the statistical analysis of big data,a business prediction model was proposed which was more suitable for traffic change by using least squares modeling,and the network guarantee rate based on this model was calculated.Capacity needs to guide university network ex-pansion and planning.